INTEGRASI ANTARA NILAI-NILAI KEHIDUPAN DI ANIME NARUTO DAN NILAI-NILAI PENDIDIKAN AGAMA ISLAM - Ni’mah Setya Asih (Institut Agama Islam Imam Ghozali, 2020)
The integration between science and Islam is considered to have many advantages. There are many institutions that apply integration between Islam and science, especially educational institutions. There are various kinds of knowledge that can be integrated with Islamic Religious Education, one of integration of scienceand Islam is the integration of Islamic Religious Education with entertainment, Specifically entertainment in this research is the Naruto anime, this research aims to find out the integration between the values of life in the Naruto anime that originates in humanity and the values contained in Islamic Religious Education.This research is a library research by taking the main data sources namely Naruto anime and supporting data in the form of articles and relevant studies. After the data is collected, then the data are analyzed using content analysis methods which are then drawn conclusions using the theory of integration.In this study it was found that there are points of similarity between the values in the life of the Naruto anime with the values in Islamic Religious Education, Following some values can be integrated between the values of life in the Naruto anime with the value of Islamic Religious Education, there are: the spirit of life, courage, compassion, solidarity, sacrifice, love of the homeland, work ethic, learning, self-confidence. These nine values have a common point in terms of both Naruto anime life values and Islamic Religious Education values, which are both teaching about humanity More specifically, the value of Islamic Religious Education integrated with Naruto Anime life values is the value of moral education to fellow humans (hablum minannnar)